Beraprost, a stable analog of prostacyclin, enhances cough reflex sensitivity to capsaicin in bronchitic patients. (1st December 2014) - Ishiura, Yoshihisa; Fujimura, Masaki; Shiba, Yasutaka; Ikeda, Hideko; Ohkura, Noriyuki; Hara, Johsuke; Kasahara, Kazuo
ABSTRACT Aims: Inflammatory mediators are involved in the pathophysiology of neutrophilic bronchial disorders presenting with chronic productive cough. Accumulating evidence indicates that prostanoids are key elements in the pathophysiology of these disorders. However, little is known about the role of prostacyclin in neutrophilic bronchial inflammation. Methods: The effect of beraprost, a chemically and biologically stable analog of prostacyclin, on cough response to inhaled capsaicin was examined in 14 patients with chronic bronchitis, a neutrophilic bronchial disorder, in a randomized, placebo-controlled crossover study. Capsaicin cough threshold, defined as the lowest concentration of capsaicin eliciting five or more coughs, was measured as an index of the airway cough reflex sensitivity. Results: After a 2-week treatment with beraprost (80 μg twice a day orally), the cough threshold was significantly (P < .05) decreased as compared with placebo [12.2 (geometric standard error of the mean [GSEM] 1.5) μM vs. 24.4 (GSEM 1.3)]. Conclusions: These findings indicate that prostacyclin is involved in the pathophysiology of cough reflex sensitivity in patients with chronic bronchitis, a frequently encountered neutrophilic bronchial disorder presenting with chronic productive cough.